Pelatihan Strategi Branding Bagi Usaha Mikro, Kecil, dan Menengah (UMKM) di Kelurahan Pancoran Mas Depok - Darmastuti, Shanti; Juned, Mansur; Saputra, Danis Tri; Nugroho, Yulan Adi; Ksatria, Nofa; Aysha, Faradilla Indah Siti (Indonesian Journal of Society Engagement, 2024)
Product marketing is one of the essential things for MSMEs to improve their business. In the current digitalization era, MSMEs must adopt and integrate technology into their business activities and carry out attractive branding of the products they market. In connection with the importance of branding, from the results of the preliminary study conducted by the community service team, it is known that there are still MSMEs in Pancoran Mas Depok that need to understand the benefits of branding in product marketing. Therefore, the team conducted training activities on branding strategies for MSME players in Pancoran Mas, Depok. This activity was carried out in several stages: coordination, pre-test filling, branding strategy training, and post-test filling. In addition to the training provided by the community service team, this community service activity also invited resource persons who are practitioners in the field of branding to give training on branding strategies in marketing products. From the training results, the participants considered the training beneficial for marketing products, especially those based on social media. The participants also thought branding through social media is essential in introducing products to consumers so business sustainability can run well.